SAMHD1 protects cancer cells from various nucleoside-based antimetabolites - Herold, Nikolas; Kutzner, Juliane; Schaller, Torsten (Cell cycle, 2017)
Recently, we demonstrated that sterile α motif and HD domain containing protein 1 (SAMHD1) is a major barrier in acute myelogenous leukemia (AML) cells to the cytotoxicity of cytarabine (ara-C), the most important drug in AML treatment. Ara-C is intracellularly converted by the canonical dNTP synthesis pathway to ara-CTP, which serves as a substrate but not an allosteric activator of SAMHD1. Using an AML mouse model, we show here that wild type but not catalytically inactive SAMHD1 reduces ara-C treatment efficacy in vivo. Expanding the clinically relevant substrates of SAMHD1, we demonstrate that THP-1 CRISPR/Cas9 cells lacking a functional SAMHD1 gene showed increased sensitivity to the antimetabolites nelarabine, fludarabine, decitabine, vidarabine, clofarabine, and trifluridine. Within this Extra View, we discuss and build upon both these and our previously reported findings, and propose SAMHD1 is likely active against a variety of nucleoside analog antimetabolites present in anti-cancer chemotherapies. Thus, SAMHD1 may constitute a promising target to improve a wide range of therapies for both hematological and non-haematological malignancies.